The Disciplinary System for Employees of the League of Arab States - ICHOUI Imad (My University, 2025)
This article studies and analyzes the disciplinary system for employees of the League of Arab States. The first part identifies the violations that require disciplinary responsibility for employees. The second part discusses the provisions regarding the disciplinary responsibility of employees of the League of Arab States, including the procedures for establishing disciplinary responsibility and the disciplinary penalties imposed on those who violate the regulations and rules of the League of Arab States. The third part addresses the guarantees of disciplinary accountability, both administrative and judicial. The article concludes with a summary of findings and suggestions.
Keywords: League of Arab States; international employee; disciplinary responsibility; obligations; Administrative Court of the League of Arab States; international administrative judiciary; disciplinary punishment; administrative investigation